EFEKTIVITAS PENGENALAN IKON BARU UNTAG SURABAYA KEPADA MAHASISWA DAN DOSEN UNTAG SURABAYA - Sayyidah, Rahmawati; Sudaryanto, Edy; Jupriono, Jupriono (Universitas 17 Agustus 1945 Surabaya, 2015)
17 August University of Surabaya is the oldest private university in Surabaya . established by thefoundation universities August 17, 1945 Surabaya abbreviated YPTA . Consists of structural foundationsas the founder of the foundation and structural University of the implementing agency in the activitiesthat occurred at the University . As one of the university in charge of public relations function inproviding information and related publications UNTAG Surabaya . PR has just launched a new iconUNTAG Surabaya as a tool related publications UNTAG Surabaya . This icon was made in order to helpthe public relations work . Effective communication can help increase public relations job in conveyingall kinds of relevant information on public UNTAG Surabaya either Internal or External . Formulation ofthe problem in this research is